Species diversity, taxonomy, multi-gene phylogeny, and divergence times of Meruliaceae (Polyporales, Basidiomycota) - Yue Li; Yi-Feng Cao; Karen K. Nakasone; Shi-Liang Liu; Man-Rong Huang; Shuang-Hui He (Mycology)
Meruliaceae is one of the three major families of the phlebioid clade in the Polyporales that consists primarily of wood-decaying species. We undertook an in-depth survey on species diversity, generic delimitations, phylogeny, and divergence times within the Meruliaceae with an emphasis on specimens from East Asia. In total, 26 genera including two new genera, Meruliella and Porophlebia, are recognised; ten new species, viz. Crustodontia vietnamensis, Luteochaete odontoidea, Meruliella hainanensis, Merulius pinicola, Mycoacia beijingensis, Phlebiporia crystallifera, P. odontoidea, Pseudophlebia vesiculosa, Scopuloides ellipsoidea, and S. grandinioides are introduced; eleven new combinations, viz. Allophlebia formosana, Aurantiopileus albidus, A. semisupina, Meruliella lindtneri, Merulius croceum, M. leptospermi, M. serialis, Phlebicolorata austroasiana, Phlebiodontia caspica, P. fissurata and Porophlebia fimbriata, and one new name, Mycoacia neotuberculata, are proposed. Noblesia is placed as a synonymy of Merulius, whereas Ceriporiopsis and Lilaceophlebia are accepted as synonyms of Mycoacia. Descriptions and illustrations are provided for the new genera and species, and discussions are provided for all 26 genera and new taxa. The molecular clock analysis results show that the Meruliaceae emerged with a mean stem age of 186.71 Mya of the early Jurassic, and the genera diverged with a mean stem age between 44.29 to 169.46 Mya.